Proportional Condylectomy Using a Titanium 3D-Printed Cutting Guide in Patients with Condylar Hyperplasia - Wenko Smolka; Carl-Peter Cornelius; Katharina Theresa Obermeier; Sven Otto; Paris Liokatis (Craniomaxillofacial Trauma & Reconstruction)
Background: The purpose of the study was to describe proportional condylectomy in patients with condylar hyperplasia using a titanium 3D-printed ultrathin wire mesh cutting guide placed below the planned bone resection. Methods: Eight patients with condylar hyperplasia underwent proportional condylectomy using an ultrathin titanium 3D-printed cutting guide placed below the planned bone resection. The placement of the guide was facilitated by the incorporation of anatomical landmarks. The accuracy of bone resections guided by such devices was evaluated on postoperative radiographs. The mean postoperative follow-up was 30 months. Results: Surgery could be performed in all patients in the same manner as virtually planned. The fitting accuracy of the cutting guides was judged as good. Postoperative radiographs revealed that the virtually planned shape of the newly formed condylar head after condylectomy could be achieved. Conclusions: In conclusion, the use of virtual computer-assisted planning and CAD/CAM-based cutting guides for proportional condylectomy in unilateral condylar hyperplasia of the mandible offers high accuracy and guarantees very predictable results.